PREVENTION OF POST-RESTORATION PAIN BY PROCESSING CARIOUS CAVITIES WITH WETTING AGENT - O.V. Lubchenko (Український стоматологічний альманах)
Abstract. Aesthetic restoration plays an indispensable part in the treatment of dental caries. Optimal materials for restorations are photopolymer composites of different groups. It is connected both with functional properties of materials, their usability, possibility of full recovery of the anatomical shape of a tooth, and with the grown of aesthetic requirements of the patients. Preparation of dental tissues for the adhesive system occupies a special place. Their condition determines the penetration depth of an adhesive and the probability of stress appearance in dentinal tubules, that subsequently leads to the development of post-restoration pain. Carrying out the steps for using a particular adhesive system dentists determine the dentin moisture by visual indicators, that is subjective, which in turn is one of the reasons of incorrect assessment of the dental tissues and may cause treatment failure and development of post-filling pain.